1985
DOI: 10.1080/01652176.1985.9693978
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the non‐involvement of the uterus in the lifespan of the corpus luteum in the cyclic dog

Abstract: SUMMARY Progesterone levels in peripheral blood of dogs were analysed during the cycle in which hysterectomy (n= 5) or sham surgery (n = 3) was performed as well as during the cycle of dogs (n = 5) hysterectomized at least one year prior to this study; the data were compared with the findings in control dogs (n=3). The averages of the duration of the luteal period observed in the three experimental groups were not significantly different from those of control dogs. Immediately after surgery, the progesterone l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
4

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 14 publications
2
46
0
4
Order By: Relevance
“…Prolactin concentrations were determined by a validated homologous RIA [23]. Canine prolactin used as standard (B31) was purified from fresh frozen whole pituitary glands [34] including gel filtration through sephadex G-100.…”
Section: Hormone Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolactin concentrations were determined by a validated homologous RIA [23]. Canine prolactin used as standard (B31) was purified from fresh frozen whole pituitary glands [34] including gel filtration through sephadex G-100.…”
Section: Hormone Analysesmentioning
confidence: 99%
“…In females, lowering of the plasma concentration of prolactin to basal level is usually associated with the return of gonadotrophic pulsatility [20,22]. In bitches, administration of dopamine agonists during both the luteal phase and anoestrus results in shortening of the interoestrous interval in the bitch [23][24][25][26]. It has been shown that this dopamine agonist-induced shortening of the interoestrous interval in the bitch is associated with an increase in circulating FSH concentration [27].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma concentrations of PRL were determined with a previously validated heterologous RIA (Okkens et al, 1985). The intra-assay and inter-assay coefficients of variation were 3.5% and 11.5%, respectively.…”
Section: Hormone Determinationmentioning
confidence: 99%
“…Ovulation was assumed to occur when the plasma progesterone concentration exceeded 16 nmol/L [9][10][11]. Blood samples were collected from the jugular vein, immediately placed in chilled lithium heparin-coated tubes and centrifuged at 4 8C for 10 min at 1500 Â g. Plasma was stored at À25 8C until assayed.…”
Section: Methodsmentioning
confidence: 99%